2014
DOI: 10.1007/s11069-014-1046-2
|View full text |Cite
|
Sign up to set email alerts
|

Bay of Bengal cyclone extreme water level estimate uncertainty

Abstract: Hawliau Cyffredinol / General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights. • Users may download and print one copy of any publication from the public portal for the purpose of private study or research. • You may not further distribute the material or use it for any profit-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Coastal flooding is defined as temporary inundation of a terrestrial area that is not normally submerged. Trends contributing to a likely future increase in coastal erosion and flooding risk include: increasing population density (Hanson et al, 2011), asset concentration in coastal areas (Hinkel et al, 2014), accelerating sea level rise (Hay et al, 2015), potential changes to storm surge climate (Bader et al, 2011; Lewis et al, 2014) and declines in sediment supply (Syvitski et al, 2005). Considering these trends, the ability of decision makers to take appropriate (politically salient, publicly acceptable and financially sustainable) mitigation and adaptation management decisions relies critically on knowledge about the functioning of coastal systems and the risks that they present.…”
Section: Introductionmentioning
confidence: 99%
“…Coastal flooding is defined as temporary inundation of a terrestrial area that is not normally submerged. Trends contributing to a likely future increase in coastal erosion and flooding risk include: increasing population density (Hanson et al, 2011), asset concentration in coastal areas (Hinkel et al, 2014), accelerating sea level rise (Hay et al, 2015), potential changes to storm surge climate (Bader et al, 2011; Lewis et al, 2014) and declines in sediment supply (Syvitski et al, 2005). Considering these trends, the ability of decision makers to take appropriate (politically salient, publicly acceptable and financially sustainable) mitigation and adaptation management decisions relies critically on knowledge about the functioning of coastal systems and the risks that they present.…”
Section: Introductionmentioning
confidence: 99%
“…The decrease of the storm surge occurred again over about 12 h, resulting in mostly symmetric hydrograph. However, extreme surges occur especially during hurricane as along the US coast (East et al, 2008;Lin et al, 2010;Ebersole et al, 2010;Needham and Keim, 2012;Chen et al, 2014;Thomas et al, 2019) or due to tropical cyclones (Lewis et al, 2014;Takagi et al, 2017;Liang et al, 2019;Yin et al, 2020). Given these obesrvations and projections, it is clear that investigations into the effect of storm surge processes on wave overtopping phenomenon are needed in order to prepare responses to future storm events and to minimize the damages.…”
Section: Field Data and Predictionsmentioning
confidence: 99%
“…Finally, the spatial and temporal coverage of the recorded storms is sparse relative to the size of the shoreline and sampling of tidal phases. Indeed, the past studies reported sensitivity of the surge level estimates to storm parameters around the Bengal delta region, both for the maximum water level (∼ O(m)) and the inundation extent (∼ O(km)) (Lewis et al, 2014;Hussain et al, 2017).…”
Section: Introductionmentioning
confidence: 99%